(untitled) (International Journal of Architecture and Urbanism, 2025)
Urbanization is a defining trend of the 21st century, with villages and towns merging into larger urban areas at an accelerating pace. This global transformation is particularly evident in developing countries, where the demand for housing is growing amidst rapid urban expansion. Currently, more than half of the world’s population resides in urban areas, and nearly 1,000 urban agglomerations with populations of over 500,000 exist, predominantly in developing nations. The world’s population, currently at 7.6 billion, is projected to grow to between 8.4 and 8.7 billion by 2030, intensifying the need for shelter, especially in urbanizing regions. Traditionally, settlements in developing nations have been located along riverbanks, but these areas are increasingly vulnerable to natural disasters. This study focuses on the decline of Malay settlements, deeply connected to the river in both cultural and livelihood aspects. The research methodology involves analyzing the morphological changes of settlements over time through historical comparisons, archival research, visual documentation, and mapping tools such as Google Earth. Additionally, CADD drawings were employed to present a detailed visualization of the case study area. The findings suggest that urbanization, combined with natural disasters such as floods, has led to the disintegration of these riverfront communities. The younger generations no longer view the river as a symbol of prosperity, marking a shift in cultural and social dynamics.